Compression-bend-shearing performance of column-to-column bolted-flange connections in prefabricated multi-high-rise steel structures. (1st April 2018) - Liu, X.C.; He, X.N.; Wang, H.X.; Zhang, A.L.
Graphical abstract: Highlights: Performance of bolted-flange connections under compression, moment and shearing. Static compression, moment and shearing tests and FEA on bolted-flange connections. Effect of flange thickness, bolt edge distance, flange edge width and bolt hole size. Stiffness and strength of connections, bolt tension and contact force were obtained. Yield bearing capacity obtained from proposed formulas agreed well with test and FEA. Abstract: The bolted-flange connection is used to connect rectangular HSS columns in prefabricated multi-story and high-rise steel structures. It may subject to coexisting axial compression, bending moments and shearing under the combination of dead, live, wind loads or earthquake action. The bearing performance is different from that of bolted-flange connections used in pipelines, towers and mast structures. To investigate the bearing performance of a connection subjected to coexisting compression, bending moments and shearing, static tests and a finite element analysis (FEA) were applied to 12 column-to-column bolted-flange connections with different flange thicknesses, bolt edge distances, flange edge widths and bolt hole diameters, as well as one column without connection. The effects of flange thickness, bolt edge distance, flange edge width, and bolt hole diameter on the stiffness and strength of connections, bolt tension levels, and contact forces between flanges were obtained as well as effects on the failure mode and mechanisms of the connections. Flange thickness was found to have a considerable impact on the performance of connections, while the bolt edge distance and flange edge width were found to have a lesser effect. The FEA results agree well with the test results, verifying the finite element model (FEM). Some performance results that could not be obtained through testing were obtained. Based on yield line theory and T-stub analogies, the load transfer mechanism of bolted-flange connections was obtained and formulas for yield-bearing capacity are proposed. The results obtained from the formulas agree well with the test and FEA results.